"Functional trapezius muscle reconstruction after resection of a desmoid tumor using an innervated gracilis free flap". Issue 1 (31st December 2022) - De Michele, Federico; Massarelli, Olindo; Franza, Mara; Gebbia, Vittorio; D'Arpa, Salvatore
Abstract: Desmoid tumors are characterized by indolent growth, progressive invasion of surrounding tissues and a high rate of relapse. We present the case of a desmoid tumor rising from the trapezius of a young woman. Following resection, we performed a functional reconstruction using an innervated gracilis free flap.